Risco, desastre e prevenção: um estudo sobre estratégias coletivas na ótica de adolescentes moradores do bairro do Jaçanã São Paulo/SP - Tavanti, Roberth Miniguine (2013)
This research aims to understand how teenagers who live in Jaçanã, a neighborhood in the North of São Paulo city, coexist with disaster risks associated with rainfall (floods, flash floods and landslides). Generally speaking, by focusing on the language of risks grounded on the perspective developed at the Center of Discursive Practices and Production of Senses in Daily Life - PUC/SP, it tries to contribute to the construction of models of observing the social phenomena that have focus on the tension between universality and particularity, between consensus and diversity, aiming to produce an useful theoretical-methodological tool to promote social change. To achieve our goals, we have performed the following procedures: 1) systematic survey of files and records concerning the official history of Jaçanã neighborhood; 2) analysis of documents relating to the mapping of risk areas and the preventive plan of Civil Defence; 3) daily records on field journals; and 4) the realization of activities (workshops about risks) with groups of teenagers inhabitants of this territory. The workshops are spaces for trading meanings, with high potential of collective significance, allowing the visibility of arguments, offsets, construction and contrast of versions and therefore privileged occasions for discursive practices analysis. As a result, an insufficient local structure and organization of institutions and services related to civil defense was identified, as well as an absence of a kind of prevention which rely on the support and participation of groups and/or vulnerable populations. In relation to the linguistic repertoires, it is important to point out the multifaceted character of senses of risk in everyday life, as well as the recurrent use of terms associated with the risks in various contexts (health, traffic accidents and household, education, sports and games, social and urban insecurity and environment). About the disaster risk prevention in the groups of teenagers, it was showed the importance of developing local alternatives focused on disaster risk management, on the basis of the following thematic axes: 1) political participation and popular mobilization of residents considered members of the various decision-making processes, in particular with regard to public policies and control mechanisms to disaster risk management; and 2) the approach of collective (associations) between the performers, groups, institutions and/or organizations related to these questions, as one of the relevant alternatives for the development of collective strategies arising from the proceedings of local disaster risk management. In short, this research, produced through the sharing of information, technologies and knowledge (managers, specialists and citizens) and purposely held in a specific context (vulnerable area), contributes to the development of instruments of control and management of risks, as well as for the construction of local alternatives (collective strategies) with emphasis in public debate around disaster risk prevention related to rainfall in urban areas